2012
DOI: 10.5923/j.ajmms.20120201.05
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Profile of Gram Negative Bacteria Isolated from Surgical Wounds in Minna, Bida, Kontagora and Suleja Areas of Niger State

Abstract: Antibiotics resistance profiles of bacteria from surgical wounds were investigated in four (4) General Hospitals (Bida, Kontagora, Minna and Suleja) in Niger State. Five hundred (500) samples (i.e. Two hundred (200) samples in Minna, One hundred (100) samples each Suleja, Kontagora and Bida) of wound exudates from these general hospitals, were analysed. The results showed the presence of Klebsiella Pneumoniae, Escherichia coli, Pseudomonas aeruginosa, and Proteus vulgaris in the samples from the wounds. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
(3 reference statements)
1
8
1
Order By: Relevance
“…However, contrary to our findings, many authors have reported higher level of resistance among infected wound isolates to aminoglycosides [2,22,24,50,51]. Aside from haphazard use of these drugs in those set ups, bacteria are able to resist the action of aminoglycosides via: i).…”
Section: Discussioncontrasting
confidence: 90%
“…However, contrary to our findings, many authors have reported higher level of resistance among infected wound isolates to aminoglycosides [2,22,24,50,51]. Aside from haphazard use of these drugs in those set ups, bacteria are able to resist the action of aminoglycosides via: i).…”
Section: Discussioncontrasting
confidence: 90%
“…In contrast, S. aureus showed very high sensitivity to cefotaxime, vancomycin, and ciprofloxacin. These findings are in consistent with the study of Adcock et al, 18 and Sani et al, 19 who recorded that pathogenic Staphylococci are resistant to several antibiotics. Resistance of this bacterium to erythromycin group tends to develop so rapidly.…”
Section: Discussionsupporting
confidence: 93%
“…The common wound pathogens include bacteria, fungi, protozoa, and viruses [13]. Common bacterial pathogens associated with wound infection include Staphylococcus aureus , Escherichia coli, Pseudomonas aeruginosa , Klebsiella pneumoniae , Streptococcus pyogenes , Proteus species, Streptococcus species, and Enterococcus species [12, 14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…The antibiotics resistant pathogens are acquired from either health care setting environment, health care personnel, or inpatients [20]. Hospital-acquired infections are further complicated by increasing prevalence of multidrug resistant bacterial pathogens like methicillin-resistant S. aureus (MRSA), methicillin-resistant coagulase negative Staphylococcus (CoNS), vancomycin-resistant Enterococcus (VRE), and polymicrobial flora and fungi [14]. …”
Section: Introductionmentioning
confidence: 99%